PENGARUH HARGA TANAMAN PANGAN TERHADAP INFLASI DI KABUPATEN KENDAL - Mardiyanto, Ilyas Cahaya; Prasetyanto, Panji Kusuma (Transpublika Publisher, 2023)
This study aims to analyze the effect of food crop prices on inflation in Kendal Regency. The increasing demand for agricultural commodities has resulted in the price of agricultural commodities increasing due to the high demand. The impact arising from the increase in the price of agricultural commodities is an increase in inflation, which causes a decrease in people's purchasing power because prices are increasingly unaffordable. The data used in this study is time series data for the period 2016 to 2022, the data used is secondary data on monthly developments in food crop prices and inflation in Kendal Regency. The tool used in this research is the analysis of the VAR/VECM (Vector Autoregression (VAR) or Vector Error Correction Model (VECM)) model with the help of the Eviews 10 application. The findings show that a number of variables, including the price of garlic, large red chilies, and Red cayenne pepper has a significant effect on inflation in Kendal Regency in the long run. In the short term, several variables such as the price of shallots and red cayenne pepper also have a significant effect on inflation in Kendal Regency.